Developing an Undergraduate Public Health Introductory Core Course Series - Nelson-Hurwitz, Denise C.; Tagorda, Michelle; Kehl, Lisa; Buchthal, Opal V.; Braun, Kathryn L. (Frontiers in Public Health, 2018)
The number of undergraduate public health education programs is increasing, but few publications provide examples of introductory public health courses that provide foundational knowledge and meet 2016 Council on Education in Public Health (CEPH) accreditation standards. This article presents the development and testing of a three-course, introductory series in public health at the University of Hawai‘i at Mānoa (UHM). Development was informed by best pedagogical practices in education, web review of existing programs, literature review, key informant interviews, and accreditation standards. Student mastery of required concepts, domains, and competencies is assessed through testing and class assignments. Data from course evaluations, students' exit questionnaires at graduation, and faculty feedback were used to continuously evolve and adapt the curriculum. The three-course series—including Introduction to Public Health, Public Health Issues in Hawai‘i, and Introduction to Global Health—was designed to provide incoming undergraduate public health students with a foundation in local, national, and global public health concepts and domains, while improving their skills in public health communication and information literacy. Data from class assignments, examinations, and later coursework suggest students are mastering the course materials and gaining required competencies. Data from course evaluation and exit questionnaires suggest that the students appreciate the series' approach and the challenge to apply course concepts locally and globally in subsequent courses. This foundational public health series provides a model for an introductory course series that can be implemented with existing resources by most programs, meets the new CEPH requirements, is well-received by students, and prepares students well for upper-division public health courses.